2008
DOI: 10.1016/j.ydbio.2008.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3 is a PI3K-dependent molecular switch controlling the initiation of oocyte growth

Abstract: In mammals, oocytes are packaged into compact structures-primordial follicles-which remain inert for prolonged intervals until individual follicles resume growth via a process known as primordial follicle activation. Here we show that the phosphoinositide 3-kinase (PI3K) signalling pathway controls primordial follicle activation through the forkhead transcription factor Foxo3. Within oocytes, Foxo3 is regulated by nucleocytoplasmic shuttling. Foxo3 is imported into the nucleus during primordial follicle assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
316
1
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(357 citation statements)
references
References 40 publications
17
316
1
12
Order By: Relevance
“…Furthermore, although the EGFR is among the tyrosine kinase receptors that can activate the phosphatidylinositol 3-kinase (PI3K) pathway (Liu et al, 2006), the intracellular signaling pathways activated during ovine primordial follicle activation remain largely uncharacterized and are fundamental to understand the molecular systems responsible for this fundamental aspect of ovarian development and function that influences fertility (John et al, 2008). Some studies have demonstrated that pharmacological manipulation of the PI3K pathway, using PI3K inhibitors such as LY294002 (Granville et al, 2006), could potentially give a better understanding of the function and regulatory mechanisms of this pathway on Anim.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although the EGFR is among the tyrosine kinase receptors that can activate the phosphatidylinositol 3-kinase (PI3K) pathway (Liu et al, 2006), the intracellular signaling pathways activated during ovine primordial follicle activation remain largely uncharacterized and are fundamental to understand the molecular systems responsible for this fundamental aspect of ovarian development and function that influences fertility (John et al, 2008). Some studies have demonstrated that pharmacological manipulation of the PI3K pathway, using PI3K inhibitors such as LY294002 (Granville et al, 2006), could potentially give a better understanding of the function and regulatory mechanisms of this pathway on Anim.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using mutant mice indicated that oocyte-specific deletion of the Phosphatase with TENsin homology deleted in chromosome 10 (PTEN) gene promotes the growth of all primordial follicles in neonatal and adult animals (3)(4)(5). The PTEN gene encodes a phosphatase enzyme that negatively regulates the PI3K-Akt signaling pathway.…”
mentioning
confidence: 99%
“…The PTEN gene encodes a phosphatase enzyme that negatively regulates the PI3K-Akt signaling pathway. Deletion of PTEN in the oocyte increases protein kinase B (Akt) phosphorylation and nuclear export of downstream Foxo3 proteins (4). Indeed, Foxo3 gene deletion also activated all dormant primordial follicles in mice (6).…”
mentioning
confidence: 99%
“…FoxO3a -/-mice exhibited global activation of primordial follicles and age-dependent infertility (8,40). Oocyte-specific ablation of phosphatase and tensin homolog (a negative regulator of PI3Ks) led to PI3K-induced Akt activation, and thus, phosphorylated FoxO3a, suppressing its activity, and consequently triggering a phenotype in oocytes equivalent to that in mice lacking FoxO3a (41,42). The reduced phosphorylation of FoxO3a observed in the present study would maintain FoxO3a localization in the nuclei, which prevents the activation of follicle development.…”
Section: Discussionmentioning
confidence: 99%